The Influence Of Repurchase Intentions Based On Brand Image, Product Quality, Trust And Safety On MOYA Soy Milk In The Area Of Tangerang City - Aulya Tsintana Fitri; Ari Apriani (Dinasti Publisher, 2024)
The consumption of soy milk in Indonesia remains relatively low in comparison to other countries within the ASEAN region. The low consumption of soy milk in Indonesia can be attributed to the fact that milk has not yet been established as a beverage culture among the public. This study aims to explain the direct relationship between brand image variables on repurchase intention, product quality on repurchase intention, trust on repurchase intention and safety on repurchase intention of MOYA soy milk products. The sample was determined as many as 105 samples. Data were collected using a questionnaire with customized criteria. The research instrument was measured using a Likert scale. The data analysis techniques used are descriptive, validity and reliability tests and T-test. The results in this study show that brand image has a positive influence on repurchase decision intentions. product quality has a positive and significant effect on repurchase intention. trust does not have a significant effect on repurchase intention. and also safety does not have a positive influence on repurchase intention for MOYA soy milk products.